Association between Metformin Use and Coronary Artery Calcification in Type 2 Diabetic Patients. (5th May 2019) - Lu, Yi; Wang, Yidong; Weng, Ting; Chen, Zexin; Sun, Xiujuan; Wei, Jia; Cai, Zhejun; Xiang, Meixiang
Abstract : Objectives . Type 2 diabetes mellitus (T2DM) is associated with coronary artery calcification (CAC) which is an independent risk factor for cardiovascular events. Metformin is the first-line antidiabetic medication. We aimed to investigate the association between metformin use and CAC. Methods . We included 369 patients with T2DM in this cross-sectional study. CAC scores, clinical characteristics, and antidiabetic drug prescription information of the patients were acquired. Baseline parameters were balanced for metformin and nonmetformin users using the propensity score matching (PSM) strategy. Results . Among the 369 subjects who met our inclusion criteria, 288 subjects were included for further analysis after PSM. Metformin prescription rather than other antidiabetic medications was related to lower CAC scores (OR [95% CI] = 0.55 [0.34–0.90];P = 0.018 ). Further multivariable logistic regression analysis demonstrated that metformin was negatively associated with CAC severity (OR [95% CI] = 0.58 [0.34–0.99];P = 0.048 ), which was independent of age, BMI, eGFR, gender, cigarette smoking, duration of diabetes, hypertension, statin prescription, and number of nonmetformin antidiabetic agents. A subgroup analysis revealed a significant association between metformin and CAC scores in smokers (OR [95% CI] = 0.38 [0.16–0.93];P = 0.035 ), but the association was not observed in never-smokers (OR [95% CI] = 0.72 [0.34–1.51];P = 0.383 ). Conclusions . Metformin usage was independently associated with lower CAC scores in T2DM patients. The negative correlation between CAC scores and metformin was most prominent in patients with a history of cigarette smoking.